2020
DOI: 10.3390/jcm9020462
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of the Transmission Risk of the 2019-nCoV and Its Implication for Public Health Interventions

Abstract: Since the emergence of the first cases in Wuhan, China, the novel coronavirus (2019-nCoV) infection has been quickly spreading out to other provinces and neighboring countries. Estimation of the basic reproduction number by means of mathematical modeling can be helpful for determining the potential and severity of an outbreak and providing critical information for identifying the type of disease interventions and intensity. A deterministic compartmental model was devised based on the clinical progression of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
512
5
9

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 1,139 publications
(540 citation statements)
references
References 30 publications
14
512
5
9
Order By: Relevance
“…where (1)- (7) for each autonomous region in Spain. The solid line is the result of the epidemic model, aggregated by ages, for the number of individuals inside compartments (H+R+D) that corresponds to the expected number of cases (see Figure 1), and dots correspond to real cases reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…where (1)- (7) for each autonomous region in Spain. The solid line is the result of the epidemic model, aggregated by ages, for the number of individuals inside compartments (H+R+D) that corresponds to the expected number of cases (see Figure 1), and dots correspond to real cases reported.…”
Section: Discussionmentioning
confidence: 99%
“…Equations (1)- (7) enable to monitor the spatio-temporal propagation of COVID-19 across Spain. To check the validity of our formalism, we aggregate the number of cases predicted for each municipality at the level of autonomous regions (comunidades autĂłnomas), which is a first-level political and administrative division, and compare them with the number of cases daily reported by the Spanish Health Ministry.…”
Section: B Prediction Of the Evolution Of Covid-19 In Spainmentioning
confidence: 99%
“…While countermeasures to prevent epidemic spread require the sort of strong political decisions that resulted in strong movement restrictions, our study indicated that the delay to a major epidemic in countries other than China (using Japan as an example) was unfortunately minimal. While the complete lockdown of Wuhan, Wenzhou, and Shenzhen likely helped reduce case incidence outside of these cities, migration from other cities in China could still contribute to the spread of infection locally and internationally [24][25][26]. To quantify the epidemiological impact for the entire course of the epidemic more precisely, a more detailed analysis using dynamic datasets, e.g., airline passenger data, should be explored in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Our objective is to develop a mathematical model, which recovers from data of reported cases, the number of unreported cases for the COVID-19 epidemic in Wuhan. For this epidemic, a modeling approach has been developed in [3], which did not consider unreported cases. Our work continues the investigation in [4,5] of the fundamental problem of parameter identification in mathematical epidemic models.…”
Section: Introductionmentioning
confidence: 99%